2021
DOI: 10.1111/tpj.15526
|View full text |Cite
|
Sign up to set email alerts
|

CCR‐NB‐LRR proteins MdRNL2 and MdRNL6 interact physically to confer broad‐spectrum fungal resistance in apple (Malus × domestica)

Abstract: Apple leaf spot, a disease caused by Alternaria alternata f. sp. mali and other fungal species, leads to severe defoliation and results in tremendous losses to the apple (Malus 3 domestica) industry in China. We previously identified three RPW8, nucleotide-binding, and leucine-rich repeat domain CC R -NB-LRR proteins (RNLs), named MdRNL1, MdRNL2, and MdRNL3, that contribute to Alternaria leaf spot (ALT1) resistance in apple. However, the role of NB-LRR proteins in resistance to fungal diseases in apple remains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Yr10 [ 39 ] and RPM1 [ 40 ] for stripe rust and Pm21 for powdery mildew resistances [ 41 ] in wheat, and Pb1 [ 42 ] for panicle blast resiatnce in rice. The NBLRRs with a RPW8-like CC domain are referred to as CCR-NBLRRs or RNLs [ 43 , 44 ]. The five EcNBLRRs, viz., EcNBLRR12, EcNBLRR65, EcNBLRR77, EcNBLRR102 and EcNBLRR105 showed RPW8 domins with CC structures at N-Terminal.…”
Section: Discussionmentioning
confidence: 99%
“…Yr10 [ 39 ] and RPM1 [ 40 ] for stripe rust and Pm21 for powdery mildew resistances [ 41 ] in wheat, and Pb1 [ 42 ] for panicle blast resiatnce in rice. The NBLRRs with a RPW8-like CC domain are referred to as CCR-NBLRRs or RNLs [ 43 , 44 ]. The five EcNBLRRs, viz., EcNBLRR12, EcNBLRR65, EcNBLRR77, EcNBLRR102 and EcNBLRR105 showed RPW8 domins with CC structures at N-Terminal.…”
Section: Discussionmentioning
confidence: 99%
“…Homogeneously, the VpRPW8s could also enhance plant resistance to P. viticola , P. capsici , and P. parasitica [ 41 ]. Additionally, MdRNL2 and MdRNL6 (encode RPW8-NBS-LRR protein) were considered to be spectrum fungal resistance genes [ 66 ]. By transient expression in tobacco leaves and overexpression in Col-WT Arabidopsis , we showed that HbRPW8-a is a broad-spectrum resistance gene with resistance to E. cichoracearum UCSC1 and Pst DC3000.…”
Section: Discussionmentioning
confidence: 99%
“…The plants were transferred to fresh medium every 4 weeks. Approximately 4-week-old apple seedlings were used in the fungal infection and toxin injection experiments when the fifth leaf of the seedling had expanded (leaf length: 2 cm) [25].…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…Plants have evolved a primary defense system that responds to pathogen-associated molecular patterns (PAMPs) via pattern recognition receptors, a signaling cascade that is termed PAMP-triggered immunity (PTI) [24,25]. PTI causes rapid defense reactions, such as the production of ROS, ion fluxes, and cell wall reinforcement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation